KONSERVASI SUMBER DAYA AIR MOLULU BERBASIS KEARIFAN LOKAL DI DESA WANGONGIRA, HALMAHERA UTARA (Studi Kasus Masyarakat Desa Wangongira, Kabupaten Halmahera Utara) - Ronald Kondo Lembang (JURNAL HUTAN PULAU-PULAU KECIL, 2017)
The existence of local wisdom applicable to a society can be utilized as one of the socio-cultural factors in order to formulate the strategy of watershed conservation because it is already embedded in an indigenous community and is very necessary to be preserved and also can have implications for the life of the community an area. The purpose of this study is to documenting the value of local wisdom of Wangongira village community in conserving water resources and implementing the value of local wisdom in community life. The method used is qualitative descriptive. Data collection using structured interview technique, limited participant observation, the secondary data tracking related to research object. The result of the research explains that the form of local wisdom in Wangongira society related to water resources protection is in the form of prohibition and absinance to take anything around the springs and doing any activity around the springs because it is believed there is a mystical thing in local language called Moro and every year people carry out the ceremony gratitude harvesting around the springs to respect the existence of the spring as a source of life. Implementation of the value of local wisdom, the community utilizes water sources for drinking and other necessities of life but not directly at the source of the spring due to the abstinence or the prohibition. The impact on water resources is maintained it is authenticity from both the good water quality and the surrounding environment.